Cross reaction and forensic comparison of blood testing done by private and public sector laboratories - Stadler, Christian; Dias Filho, Claudemir Rodrigues; Roca, Maria Gabriela (Revista Brasileira de Criminalística, 2017)
Blood evidence consists of one of the most important forensic pieces. However, it is not always easy to identify a stain as blood. The best and fastest way of doing so, is by using rapid screening derived from immunochromatographic tests to spot hemoglobin. However, cross reaction between species might be an issue since hemoglobin of other animals could be present, especially considering crimes against fauna, outdoor crime scenes with an easy access for animals, and human and domestic animal trauma cases. According to the particular structure in each country there are private and/or public laboratories working in this field. Methods and resources from private and public sectors are different, and procedures also differ from country to country. The main objective of our work was to validate the presence of human blood using interspecific samples and the criteria defined by each lab using rapid blood detection test kits from the public sector related to forensic analysis in Brazil and from the private sector in Germany. As a secondary goal, we have evaluated sensibility, the Hook Effect and pH effect in some commercially available kits. Our results showed that the tests carried out are suitable for the detection of human blood in forensic samples using methods commonly employed in the public and private sectors.